OP0303 Systematic screening of comorbidities improves vaccination rates, skin cancer screening and vitamin d supplementation in patients with axial spondyloarthritis: results of the comedspa prospective, controlled, one year randomised trial. (12th June 2018) - Moltó, A.; Etcheto, A.; Poiraudeau, S.; Gossec, L.; Claudepierre, P.; Soubrier, M.; Fayet, F.; Wendling, D.; Gaudin, P.; Dernis, E.; Guis, S.; Pouplin, S.; et al.
Abstract : Background: Specific recommendations for the detection/prevention of comorbidities have been proposed for patients with SpA. However, we know that often a gap exists between recommendation and their implementation in daily practice Objectives: To evaluate the impact of a program of systematic screening of comorbidities and its management (detection/prevention). Methods: Prospective, randomised controlled open, 12 month trial (NCT02374749 ). Patients: Axial SpA (according to rheumatologist). Study treatment: Collection of data by the nurse during a specific out-patient visit for the 5 studied SpA comorbidities (i.e. cardiovascular disease (CVD), osteoporosis, cancer, infection and peptic ulcer) according to the recommendations of the French Society of Rheumatology. In the event of non-agreement with the recommendation the patient was informed. A report summarising the results of this program prepared by the nurse was sent to the patient's attending physician and rheumatologist. Treatment allocation: After written informed consent, the study treatment was allocated randomly. Outcome variables: the main outcome was the change after one year of a comorbidity score. This weighted composite comorbidity score ranged from 0 to 100, where 0=optimal management of the 5 studied comorbidities and its weights were derived from the percentage of attributed mortality in SpA to each comorbidity in the literature, i.e. 40 points for CV disease, 20 points for cancer and infection, 10 points for osteoporosis and 10 points for peptic ulcer. The number of patients with actions undertaken against comorbidities according to the recommendations during the 12 months following this program were defined as secondary variables Results: There were no differences in the baseline characteristics of the 502 recruited patients (252 and 250 in the active and control groups, respectively): Age: 46.7±12.2 years, male gender: 62.7%, disease duration: 13.7±11.0 y, Xray sacroiliitis 62.8%, MRI sacroiliitis 65.7%, current biologic treatment: 78.3%, ASDAS-CRP: 1.9±0.8, BASFI: 25.6±22.3. During the 1 year follow-up period, the comorbidity score decreased more in the active group, but this difference was not significant (−3, 20 vs −1.85). The number of actions per patient was statistically higher in the group comorbidities : 4.54±2.08 vs 2.65±1.57 (p<0.001); the number of patients with actions performed to be in agreement with recommendations during the 12 months follow-up was higher in the active group for infections (flu vaccination : 28.6% vs 9.9%, p<0.01; pneumococcal vaccination:40.0% vs 21.1%, p=0.04), skin cancer screening (36.3% vs 17.2%; p=0.04), and osteoporosis (BMD performed: 22.6% vs 8.7%, p<0.01; Vitamin D supplementation initiation: 51.9% vs 9.4%, p<0.01). Conclusions: This study highly suggests the short-term benefit of program on the systematic screening of comorbidities for its management in agreement with recommendations, even if this young age population of axSpA patients. Acknowledgements: This study was conducted thanks to a grant from the French National Research Program (PHRC) thanks to an unrestricted grant from ABBVIE. Disclosure of Interest: None declared